Enzyme Catalyzed Copolymerization of Lignosulfonates for Hydrophobic Coatings - Mayr, Sebastian A.; Schwaiger, Nikolaus; Weber, Hedda K.; Kovač, Janez; Guebitz, Georg M.; Nyanhongo, Gibson S. (Frontiers in Bioengineering and Biotechnology, 2021)
Enzymatic polymerization of lignin can generate a variety of value-added products concomitantly replacing fossil-based resources. In line with this approach, a laccase from the thermophilic fungus Myceliophthora thermophila (MtL) was used to couple a hydrophobicity enhancing fluorophenol (FP) molecule, namely 4-[4-(trifluoromethyl)phenoxy]phenol (4,4-F3MPP), as a model substrate onto lignosulfonate (LS). During the coupling reaction changes in fluorescence, phenol content, viscosity and molecular weight (GPC) were monitored. The effects of enzymatic coupling of FP onto LS on hydrophobicity were investigated by the means of water contact angle (WCA) measurement and determination of swelling capacity. Full polymerization of LS resulting in the production of water-insoluble polymers was achieved at a pH of 7 and 33°C. Incorporation of 2% (w/v) of FP led to an increase in WCA by 59.2% while the swelling capacity showed a decrease by 216.8%. Further, FTIR and XPS analysis indicated successful covalent coupling of the FP molecule onto LS by an emerging peak at 1320 cm-1 in the FTIR spectrum and the evidence of Fluor in the XPS spectrum. This study shows the ability of laccase to mediate the tailoring of LS properties to produce functional polymers.